Preparation, Structure, and Properties of 3,3,5,5-Tetrakis(trifluoromethyl)-4H-1λ4,2,4,6-thiatriazine - David J. Brauer; Alois Haas; Keith E. Peterman; Matthias Rieland (CHIMIA)
Condensation of (CF3)2C=NLi with Cl3S3N3 in boiling CCl4 gives presumably the intermediate (CF3)2C=N–SN, which forms with excess (CF3)2C=NLi in the presence of moisture by a [2 + 4]-cycloaddition the isolated thiatriazine. A X-ray structure determination of the new compound as well as IR, NMR, and mass spectra are provided.